PROBLEMS IN THE DIAGNOSIS AND TREATMENT OF ANCA-ASSOCIATED SYSTEMIC VASCULITIS: IN THE FOCUS OF ANCA-NEGATIVE PAUCI-IMMUNE GLOMERULONEPHRITIS - T. V. Beketova; N. F. Frolova; E. S. Stolyarevich; M. Yu. Volkov; O. N. Kotenko; E. N. Aleksandrova (Научно-практическая ревматология)
One of the most common  causes of rapidly progressive glomerulonephritis (GN)  is the so-called pauci-immune crescentic GN that is characterized  by no luminescence  in kidney tissue samples during immunofluorescence microscopy and by the hyperproduction of antineutrophil cytoplasmic antibodies (ANCA). At the same time, serum ANCAs are absent in a number of cases of pauci-immune GN. Based on their own experience, the authors present the clinical and morphological characteristics of patients with ANCA-negative  pauci-immune GN and analyze the data available in the literature.Subjects and methods. This retrospective study included 8 patients with ANCA-negative  pauci-immune GN,  who were followed up at two Russian centers (the Center of Nephrology and the Center of Rheumatology) in 2011 to 2015. Results and discussion. According to our data, ANCAs are not detectable in 6% of the patients with ANCA-associated systemic vasculitis (SV) with renal involvement and/or pauci-immune GN.  The mean age at onset of the disease in the ANCA-negative  patients was 50±18 years (range 19 to 74 years); the male/female  ratio was 1:1. Four (50%) cases were diagnosed with microscopic polyangiitis; 2 cases had granulomatosis with polyangiitis; isolated renal injury was present in other 2 patients. The Birmingham SV activity index averaged 19.6±7.9.  Hematuria  was observed in all cases and it was massive in 4. The mean daily urinary protein level was 3.4±2.7 g; three (38%) patients were observed to have nephrotic  syndrome. The blood creatinine  level averaged 704±405 μmol/l;  GN was characterized  by a rapidly progressive course in 6 (75%) patients; hemodialysis was needed in 5. A morphological study of the kidney determined  crescents (in on an average of 52 glomeruli) in the majority of cases and glomerulosclerosis in one patient. All the patients were observed to have varying degrees of interstitial fibrosis. Three (38%) treated patients achieved remission. The mortality rates were 38%. Interestingly,  the data from our group as well those obtained by the study of European  cohorts were slightly different from those of the studies conducted  in Asia, according to which a renal biopsy more frequently revealed glomerular crescents; the levels of protein in the urine were higher and renal survival was worse.Thus, serum ANCAs are absent in 3–39% of cases of pauci-immune crescentic GN,  but the clinical and morphological picture corresponds to ANCA-associated  SV. A kidney biopsy helps establish the correct diagnosis, timely use induction  treatment, and improve prognosis.